Genetic variants of GRK4 influence circadian rhythm of blood pressure and response to candesartan in hypertensive patients. (3rd October 2021) - Cao, Nian; Tang, Hui; Tian, Miao; Gong, Xue; Xu, Zaicheng; Zhou, Binqing; Lan, Cong; Chen, Caiyu; Qu, Shuang; Zheng, Shuo; Ren, Hongmei; Fan, Chao; et al.
ABSTRACT: Background : Genetic variants of coding genes related to blood pressure regulation participate in the pathogenesis of hypertension and determines the response to specific antihypertensive drugs. G protein-coupled receptor kinase 4 (GRK4) and its variants are of great importance in pathogenesis of hypertension. However, little is known about role of GRK4 variants in determine circadian rhythm of blood pressure and response to candesartan in hypertension. The aim of this study was to analyze the correlation of GRK4 variants and circadian rhythm of blood pressure, and to explore their effect on antihypertensive efficiency of candestartan. Methods: In this study, a total of 1239 cases were eligible, completed ambulatory blood pressure monitoring (ABPm) observation and exon sequencing of G protein-coupled receptor kinase 4 (GRK4). ABPm was obtained before and after 4-week treatment of candesartan. Diurnal variation of systolic blood pressure and antihypertensive effect of candesartan were then assessed. Results: Compared to GRK4 wild type (GRK4-WT), patients with GRK4 variants were more likely to be non-dippers ( odds ratio (OR) 6.672, 95% confidence interval (CI) 5.124–8.688, P < .001 ), with GRK4 A142V (OR 5.888, 95% CI 4.332–8.003, P < .001), A486V (OR 7.102, 95% CI 5.334–9.455, P < .001) and GRK4 R65L (OR 3.273, 95% CI 2.271–4.718, P < .001), respectively. Correlation analysis revealed that non-dippers rhythm of blood pressure were associated with GRK4 variants (r = .420, P < .001), with GRK4 A142V (r = .416, P < .001), A486V (r = .465, P < .001) and GRK4 R65L (r = .266, P < .001), respectively. When given 4-week candesartan, patients with GRK4 variants showed better antihypertensive effect as to drop in blood pressure (24 h mSBP, 21.21 ± 4.99 vs 12.34 ± 4.78 mmHg, P < .001 ) and morning peak (MP-SBP, 16.54 ± 4.37 vs 11.52 ± 4.14 mmHg, P < .001 ), as well as greater increase in trough to peak ratio (SBP-T/P, . 71 ± .07 vs .58 ± .07, P < .001 ) and smoothness index (SBP-SI, 1.44 ± .16 vs 1.17 ± .11, P < .001 ) than those with GRK4 WT. Conclusion: This study indicates that hypertensive patients with GRK4 variants are more likely to be non-dippers. What's more, patients with GRK4 variants possess a significantly better antihypertensive response to candesartan than those with GRK4 WT.